2022
DOI: 10.21037/jtd-22-632
|View full text |Cite
|
Sign up to set email alerts
|

Identification of hub genes and their correlation with immune infiltration in coronary artery disease through bioinformatics and machine learning methods

Abstract: Background: Coronary artery disease (CAD) is a multifactorial disease and its pathogenesis remains unclear. We aimed to explore the optimal feature genes (OFGs) for CAD and to investigate the function of immune cell infiltration of CAD. It will be helpful for better understanding of the pathogenesis and the development of genetic prediction of CAD.Methods: Datasets related to CAD were obtained from the Gene Expression Omnibus (GEO) database.Cases from the datasets met diagnostic criteria including clinical sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…Inflammation in rosacea and acne can be aggravated by polarizing macrophages towards the M1 phenotype 94 97 , indicating that macrophages play a crucial role in the pathogenesis of these two diseases. Previous studies have shown a significant positive correlation between MMP9 expression and M0 macrophages infiltration in inflammation-related diseases, such as coronary artery disease (CAD), AS, adhesive capsulitis, and cancers 98 101 . However, the causal relationship between them has not yet been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation in rosacea and acne can be aggravated by polarizing macrophages towards the M1 phenotype 94 97 , indicating that macrophages play a crucial role in the pathogenesis of these two diseases. Previous studies have shown a significant positive correlation between MMP9 expression and M0 macrophages infiltration in inflammation-related diseases, such as coronary artery disease (CAD), AS, adhesive capsulitis, and cancers 98 101 . However, the causal relationship between them has not yet been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Peli1 has been proposed as a potential predictive biomarker for coronary artery disease ( 130 ). Peli1 plays a protective role in atherosclerosis as its deficiency increases pathogenic immune cell subsets (Th1 cells and Tfh cells)and decreases protective subsets (Treg and Breg cells), promoting systemic inflammation, immune cell infiltration, and foam cell formation in vascular smooth muscle cells, thereby exacerbating atherosclerosis ( 131 ).…”
Section: Diseases Involved In Peli1mentioning
confidence: 99%
“…Another study that claims to be the first of its kind developed an ML-based classification approach to discover infectious disease-associated host genes and achieved the highest accuracy for a deep neural network (DNN) model with 16 selected features ( Barman et al, 2019 ). A study by Huang et al (2022) used bioinformatics methods along with SVM recursive feature elimination (SVM-RFE) and RF algorithms to identify hub genes in coronary artery disease. Our group recently used non-negative matrix factorization (NMF) to show that this method significantly improves the enrichment detection of glaucoma genes over the traditional differential gene expression analysis.…”
Section: Introductionmentioning
confidence: 99%